Crossroad of Tradition and Innovation – The Application of Lactic Acid Fermentation to Increase the Nutritional and Health-Promoting Potential of Plant-Based Food Products – a Review - Anna Maria Ogrodowczyk; Natalia Drabińska (Polish Journal of Food and Nutrition Sciences)
Lactic acid (LA) fermentation of plant-based products is a commonly used process all over the world. Recently, except for extending the shelf-life of food and improving its palatability, the popularity of fermented food increased because of their nutritional and health-promoting quality. In this review, the existing knowledge about the effects of LA fermentation in different types of plant-based food matrices on their nutritive and health-promoting potential is presented and discussed based on the most recent studies. Furthermore, the toxicological and unfavorable effects are addressed. This review shows that although the biotransformation of several nutrients and bioactive compounds and the strain-dependent properties need more in-depth elucidation in several matrices, the recently published studies proved that LA-fermented cereals, fruits, vegetables, legumes, and seaweeds are good sources of health-promoting molecules. The obtained products offer a good alternative for a growing number of vegans, vegetarians, and flexitarians, who look for the plant-based, healthy alternatives. However, still more clinical trials evaluating the effect of their consumption on the human health are in demand.